2018
DOI: 10.1186/s40529-018-0233-y
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear dynamics in the homothallic ascomycete Sordaria fimicola

Abstract: BackgroundThe coprophilous ascomycete Sordaria fimicola usually reproduces sexually. Sexual differentiation in S. fimicola is accompanied by cellular and morphological changes, followed by multicellular tissue development to complete the sexual cycle. Although the morphological features of the sexual reproductive structure in S. fimicola have been well characterized, little is known about the nuclear dynamics and organization during these processes. Therefore, in this study, we successfully developed an Agroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Previous studies reported that light responses in S. fimicola include carotenoid accumulation and phototropism of the perithecial beak. Recently, a gene delivery system and cytological fluorescence study in S. fimicola was reported (44). The goal of this work was to gain a fundamental understanding of blue-light signal transduction in S. fimicola for sexual development, carotenoid biosynthesis, and phototropism.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies reported that light responses in S. fimicola include carotenoid accumulation and phototropism of the perithecial beak. Recently, a gene delivery system and cytological fluorescence study in S. fimicola was reported (44). The goal of this work was to gain a fundamental understanding of blue-light signal transduction in S. fimicola for sexual development, carotenoid biosynthesis, and phototropism.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleic acid manipulation and analysis. For PCR screening and Southern blot analysis, genomic DNA (gDNA) of S. fimicola was extracted by using modified cetyltrimethylammonium bromide (CTAB) method as previously described (44). Briefly, Sordaria strains were grown on cellophane-covered malt extract agar I medium, and mycelia grown on cellophane were peeled and dipped into liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations